2016
DOI: 10.1002/2016jc012044
|View full text |Cite
|
Sign up to set email alerts
|

Temporal variability of diapycnal mixing in the northern South China Sea

Abstract: Temporal variability of diapycnal mixing over 7 months in the northern South China Sea was examined based on McLane Moored Profiler observations from 850 to 2200 m by employing a finescale parameterization. Intensified diffusivity exceeding the order of 10−3 m2/s in magnitude was found over the first half of October 2014, and from 2 December 2014 to 21 January 2015 (a typical wintertime). Strong internal tides and winds in winter were the likely candidates for the high‐level diapycnal mixing in winter. As for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…It is reasonable to expect that the dissipation of mesoscale eddy energy is a possible mechanism to maintain turbulent mixing in the SCS. Although a few studies tried to explore the influence of mesoscale eddies on the turbulent mixing in the SCS 21,22 , the relationship between eddy dissipation and mixing are needed to be improved. The goal of this study is to inspect possible contribution of mesoscale eddies to small scale mixing using numerical simulation with a high horizontal resolution of 1/30° (see Methods).…”
Section: Introductionmentioning
confidence: 99%
“…It is reasonable to expect that the dissipation of mesoscale eddy energy is a possible mechanism to maintain turbulent mixing in the SCS. Although a few studies tried to explore the influence of mesoscale eddies on the turbulent mixing in the SCS 21,22 , the relationship between eddy dissipation and mixing are needed to be improved. The goal of this study is to inspect possible contribution of mesoscale eddies to small scale mixing using numerical simulation with a high horizontal resolution of 1/30° (see Methods).…”
Section: Introductionmentioning
confidence: 99%
“…Those 410 studies are difficult to arrange with conventional research vessel surveys only. Autonomous measurement platforms, such are profiling moorings (Lips et al, 2016;Sun et al, 2016), moored sensor chains (Bailey et al, 2019;Venkatesan et al, 2016), which allow capturing the variability in necessary vertical-temporal resolution can be used. Underwater gliders (Liblik et al, 2016;Rudnick, 2016) might be complicated to use due to strong tidal velocities and heavy ship traffic, but are worthy to consider as well.…”
Section: Discussionmentioning
confidence: 99%
“…As pointed out by Hui and Xu (), the total surface currents in the open ocean are mainly determined by the Ekman currents and geostrophic currents. H. Sun, Yang, et al () and S. Sun, Fang, et al () showed that the geostrophic currents generated by mesoscale eddies can significantly change the SST when there was a SST front. As shown in Figure , the GCA is much smaller than the local AGC but is significant along Transects A and B (28 ± 10 cm/s).…”
Section: Scaling Of Tke Dissipation Ratementioning
confidence: 99%
“…The enhanced surface TKE dissipation rates observed in the Kuroshio Extension region can be well scaled by an empirical scaling that considers the EBF and the wind (D'Asaro et al, ; Nagai et al, ). The mesoscale eddies also have important effect on turbulence mixing (H. Sun, Yang, et al, ; S. Sun, Fang, et al, ; Yang et al, , ). Recent observations have shown that active submesoscale motions exist in the periphery of mesoscale eddies and can significantly elevate the TKE dissipation rates in the mixed layer (Yang et al, ).…”
Section: Introductionmentioning
confidence: 99%